Conformational switching of ethano-bridged Cu,H2-bis-porphyrin induced by aromatic amines - Bettini, Simona; Maglie, Emanuela; Pagano, Rosanna; Borovkov, Victor; Inoue, Yoshihisa; Valli, Ludovico; Giancane, Gabriele (Beilstein Journal of Nanotechnology, 2015)
Cu,H2-bis-porphyrin (Cu,H2-Por2), in which copper porphyrin and free-base porphyrin are linked together by an ethano-bridge, was dissolved in chloroform and spread at the air/liquid subphase interface of a Langmuir trough. The bis-porphyrin derivative, floating film was characterized by reflection spectroscopy and the surface pressure of the floating film was studied as a function of the mean area per molecule. When aromatic amines are dissolved in the subphase, an evident interaction between the bis-porphyrin host and the aromatic amine guest is observed. A clear-cut variation of the profile of surface pressure vs area per molecule curve is observed. Reflection spectroscopy highlights that the aromatic amines dissolved in the subphase are able to induce the syn-to-anti conformational switching in the bis-porphyrin derivative. The Langmuir–Schaefer technique has been used to transfer the floating bis-porphyrin film (when using pure water as a subphase) to a surface plasmon resonance (SPR) substrate and the resulting device was able to detect the presence of aniline at concentrations as low as 1 nM in aqueous solution. The high selectivity of the SPR sensing device has been verified by checking the spectral response of the active layer towards other analytes dissolved in the aqueous solutions.
Keywords: aromatic amines; bis-porphyrin; conformational switching; Langmuir film; surface plasmon resonance